TEXT TYPES IN THE FRAME OF GENRE APPROACH - Riswanto Hosen; Kasmaini - (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
The genre-based approach has been known to characterize pedagogical practices during the implementation of the 2006 school-level curriculum.  Despite its prevalent use and  overwhelming support by school stakeholders,  the efficacy of this approach was nonetheless questionable. This paper aims to revisit the 2006 School level curriculum, its plausibility and  compatibility with individual contexts and  its bearing on EFL practices. It also discusses the  Genre- based approach in terms of its  underlying paradigms, and  possible variables and contextual factors which might  have impinged on its implementation. Some  research findings on the  adoption of the  approach in Southeast Asia context are also presented to provide insights into how the Genre-based approach could  be efficiently  adopted. This essay con- cludes with some  ideas  for the  amendment to the  2006 school- level curriculum and  how the  genre-based approach might  still be relevant in the context of teaching writing skills at tertiary education